(3cJGH aj GdfMhs - (3GdbGSe Hf Ydj Hf eMeO Hf YKeGf, CHh eMeO GdMQjQj GdHUQj , J (B516 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdMQjQi QMeg Gddg Cbhd ef HYO EaJJGM Gdbhd HMeO Pi GdWhd GdTOjO GdMhd hjGSGFdi Yf GdcdGe GdefJXe MOkG hfhYkG hGdMce jfbSe s
(3BNQgG (B:s
(3aGfXQ EdjgG fXQ GdeSJMSf hMSf GdXf hGMSf hEf JLO YjHkG aSO GdNddG aLd ef dGYjH ajg hYdG hGdMeO ddg Ydi eG Chdi afYe eG Chdi hfYe Gdehdi hGddg CYde JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B108s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdfMhs